The genus Stachybotrys (anamorphic fungi) in the semi-arid region of Brazil - Izabel,Tasciano dos Santos Santa (2010)
(The genus Stachybotrys (anamorphic fungi) in the semi-arid region of Brazil). Stachybotrys is characterized by macronematous, mononematous, unbranched or branched conidiophores, with discrete terminal and phialidic conidiogenous cells, and aseptate, reniform, ellipsoidal to spherical, smooth or verrucose conidia, which are produced in a slimy mass. Eight species have been reported from Brazil, occurring in the soil, air and leaf litter. During investigation of conidial fungi on decaying leaf litter in semi-arid areas of Brazil nine species were found: S. bisbyi (Sriniv.) G.L. Barron, S. chartarum (Ehrenb.) S. Hughes, S. globosa P. C. Misra & S. K. Srivast., S. kampalensis Hansf., S. longispora Matsush., S. nephrospora Hansf., S. nilagirica Subram., Stachybotrys parvispora S. Hughes and S. verrucispora Matsush. Stachybotrys nilagirica is a new record from Brazil. Descriptions, comments, geographic distribution and illustrations are presented for above mentioned species. A key for all species recorded in semi-arid region of Brazil is presented.